Transient abnormal myelopoiesis at birth in an infant with Down syndrome: A unique entity - Vechangi, Bindhu; Gupta, Gaurav; Umasanker, Swati; Gupta, Priyanka; Mohan, Kriti; Singh, Neha; Bhat, Nowneet Kumar; Chacham, Swathi (Indian Journal of Child Health, 2020)
Transient abnormal myelopoiesis (TAM) is a hematological disorder, which is rare but unique for children with Down syndrome. It is important to diagnose this entity, as these children are at 500 times higher risk for the development of acute myeloid leukemia (AML) later in life. We report a late-preterm, low birth weight, female baby born to a 35-year-old G4P2L2A1 mother. The baby was diagnosed to have down’s phenotype at birth. On the day one of life, the baby had leukocytosis with increased peripheral blast cells. On 23rd day of life, there was a resolution of leukocytosis and the disappearance of blast cells. The child has been under regular follow-up since then. As these children are at a high risk for the development of AML in later life, a hemogram with total leukocyte counts and differential count should be a part of neonatal follow-up.